Breast artery calcification as an opportunistic predictor of cardiovascular disease - Okşul, Metin; Şener, Yusuf Ziya; Sarıkaya, Yasin; Sarıkaya, Sevtap; Yıldırım, Arzu; Canpolat, Uğur; Akpınar, Meltem Gülsün; Hazırolan, Tuncay; Özer, Necla; Tokgözoğlu, Sadberk Lale (Springer, 2023)
Background Atherosclerotic cardiovascular disease is still the leading cause of mortality for women. Breast cancer screening with mammography is recommended in all women aged over 40 years. Aims Whether breast artery calcification (BAC) is associated with cardiovascular disease is not clear. We aimed to evaluate the association between BAC and the presence of coronary atherosclerosis determined by CT. Methods All patients who underwent both mammography and coronary CT angiography between January 2010 and December 2016 were screened, and patients with a duration of less than 12 months between CT and mammography were included. Results A total of 320 women were included and BAC was detected in 47 (14.6%) patients. BAC was correlated with age and CT coronary calcium score. Both the frequency of critical coronary artery stenosis (34% vs 10.6%; p = 0.001) and CT coronary calcium score (5.5 vs 0; p = 0.001) was significantly higher in patients with BAC. The absence of BAC was a strong predictor of the absence of significant coronary artery disease (p = 0.001). BAC was independently associated with all-cause mortality after excluding patients with breast cancer (HR: 5.32; p = 0.013). Conclusion Breast artery calcification is associated with coronary calcium score and significant coronary stenosis. A high BAC score is related to increased mortality.
Keywords: Breast Artery Calcification; Cardiovascular Risk; Coronary Calcium Score